CD4+ regulatory T cells and CD4+ activated T cells in new active and relapse tuberculosis - Ndishimye, Pacifique; Zakham, Fathiah; Musanabaganwa, Clarisse; Migambi, Patrick; Mihai, Cenariu; Soritau, Olga; El Mzibri, Mohammed; Pop, Carmen Monica; Mutesa, Leon (Cellular and Molecular Biology, 2019)
The aim of the present study was to examine characteristics of tuberculosis (TB) patients with different clinical forms and to study the frequency of Regulatory T cells (Treg cells) and Activated T cells in patients with new active and relapse TB. Forty-five pulmonary TB patients and a control group of 15 healthy individuals were enrolled in this study. Of the 45 TB patients, 15 were new cases with drug-susceptible active TB and 30 were relapsed cases (15 drug-susceptible and 15 multidrug resistant-TB). The age of study participants ranged from 21 to 68 years old. According to sex presentation, males were appreciably highly affected than females with a sex ratio of 2. The patients reported a mean recent weight loss of 8.9 kg. The Erythrocyte Sedimentation Rate was high in TB group, far exceeding the normal value. The results revealed that the number of CD3+ CD4+ T-cells significantly decreased whereas the level of blood Treg cells and expression of activation markers CD38 and HLA-DR on CD4+ T-cells significantly increased in TB group compared with the control group (p<0.05). The frequency of Treg cells was significantly higher in the TB group than the control group. Both the patients with new active TB and relapse TB demonstrated significantly higher levels of CD4+FoxP3+ Treg compared to healthy subjects (p<0.05). A high and significant percentage of Treg cells were found in patients with DS active TB than patients with MDR relapse TB. Interestingly, the frequency of CD4+FoxP3+ cells also differs according to the sputum smear microscopy status. The presence of high numbers of Treg cells and corresponding high immune activation may be an unfavourable factor that can predispose individuals to different clinical forms of TB, including relapse TB.